Analisis Daya Saing Porang di Pasar Global (Studi Kasus: Kecamatan Saradan, Kabupaten Madiun) - Putra, Demmy Filsafa Ratna; Kumalasari, Dwi Apriyanti; Trisulo, Trisulo (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
Abstract Porang is a tuber commodity that has a high selling value in the global market so that many farmers do farming in Indonesia. One of the porang centers in Indonesia is Saradan District, Madiun Regency. The main challenge that porang farmers complain about is the volatility of output prices due to the closure of the Indonesian porang export market by China. The reason is that the quality of porang in Indonesia is not worth trading in the global market. In addition, farmers also face problems with financing, especially in terms of purchasing bulbils (seeds). In order to assist farmers in overcoming these challenges. The objectives of the study are 1) to determine the comparative advantage and competitive advantage of porang in Saradan District, Madiun Regency and 2) to determine whether there arechanges in input-output prices on the comparative advantage and competitive advantage of porang in Saradan District, Madiun Regency. The approachused is Policy Analysis Matrix. The results of the above analysis can be concluded that the competitive advantage and comparative advantage of porang are very good, this is because the value of KP and KPE is less than 1.